2016
DOI: 10.2147/dddt.s102883
|View full text |Cite
|
Sign up to set email alerts
|

The combination of blueberry juice and probiotics reduces apoptosis of alcoholic fatty liver of mice by affecting SIRT1 pathway

Abstract: PurposeTo explore the effects of the combination of blueberry juice and probiotics on the apoptosis of alcoholic fatty liver disease (AFLD).MethodsHealthy C57BL/6J mice were used in the control group (CG). AFLD mice models were established with Lieber–DeCarli ethanol diet and evenly assigned to six groups with different treatments: MG (model), SI (SIRT1 [sirtuin type 1] small interfering RNA [siRNA]), BJ (blueberry juice), BJSI (blueberry juice and SIRT1 siRNA), BJP (blueberry juice and probiotics), and BJPSI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Alcohol can inhibit AMPK phosphorylation, and increase the expression of SREBP1 and suppressed adenylyl cyclase activity, finally contributing to hepatic steatosis (Subauste and Burant, 2007;Yao et al, 2017a;Yao et al, 2017b). Studies have shown that both Sirt1 and AMPK are two key factors in controlling lipid metabolism (Zhu et al, 2016). Activated Sirt1 could promote AMPK phosphorylation, and it also can be regulated by phosphorylation AMPK on the contrary, while loss of Sirt1 could increase hepatic steatosis and inflammation in mice (Choi et al, 2015;Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol can inhibit AMPK phosphorylation, and increase the expression of SREBP1 and suppressed adenylyl cyclase activity, finally contributing to hepatic steatosis (Subauste and Burant, 2007;Yao et al, 2017a;Yao et al, 2017b). Studies have shown that both Sirt1 and AMPK are two key factors in controlling lipid metabolism (Zhu et al, 2016). Activated Sirt1 could promote AMPK phosphorylation, and it also can be regulated by phosphorylation AMPK on the contrary, while loss of Sirt1 could increase hepatic steatosis and inflammation in mice (Choi et al, 2015;Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of lemon juice could dose-dependently alleviate alcohol-induced lipid accumulation and peroxidation in the liver [ 95 ]. Also, oral intake of blueberry juice could alleviate AFLD in C57BL/6J mice through inhibiting apoptosis by upregulating SIRT1 and downregulating the forkhead box protein O1 (FOXO1) signaling pathway [ 96 ]. Moreover, polyphenols extracted from blueberry could accelerate lipid clearance to ameliorate hepatic steatosis in C57BL/6J mice by promoting autophagy [ 97 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
“…Several therapeutic interventions have been identified as effective approaches in alleviating liver injury through the modulation of SIRT1. These interventions include hypothermic machine perfusion ( Zeng et al, 2017 ), treatment with partially hydrolyzed guar gum ( Liu et al, 2019b ), ischemic preconditioning ( Pantazi et al, 2014 ), the combined administration of blueberry juice and probiotics ( Zhu et al, 2016 ; Fan et al, 2021 ), as well as carbon monoxide therapy ( Sun et al, 2017 ; Kim et al, 2015 ).…”
Section: Survey Methodologymentioning
confidence: 99%